2023
DOI: 10.1126/scitranslmed.ade3157
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte CYR61 polarizes profibrotic macrophages to orchestrate NASH fibrosis

Meghan Mooring,
Grace A. Yeung,
Panu Luukkonen
et al.

Abstract: Obesity is increasing worldwide and leads to a multitude of metabolic diseases, including cardiovascular disease, type 2 diabetes, nonalcoholic fatty liver disease, and nonalcoholic steatohepatitis (NASH). Cysteine-rich angiogenic inducer 61 (CYR61) is associated with the progression of NASH, but it has been described to have anti- and proinflammatory properties. We sought to examine the role of liver CYR61 in NASH progression. CYR61 liver-specific knockout mice on a NASH diet showed improved glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The fluorescence intensity of CS-NPs/VDGtreated group was even lower than that of control group, which may be explained by that in vitro cultured HSCs would be partially activated when cultured in 10% FBS DMEM. [40] In a further experiment, HSCs-LSECs coculture system was applied to explore the possibility of inhibiting HSCs activation to prevent the loss of fenestrae and phenotype transformation of LSECs (Figure 3G). Immuno-staining of CD31 (a classic marker of capillarized LSECs) showed that HSCs pretreated with TGF-𝛽 and CS-NPs/VDG could reverse LSECs capillarization process.…”
Section: Interruption Of Hscs-lsecs Crosstalk By Cs-nps/vdg In Vitromentioning
confidence: 99%
“…The fluorescence intensity of CS-NPs/VDGtreated group was even lower than that of control group, which may be explained by that in vitro cultured HSCs would be partially activated when cultured in 10% FBS DMEM. [40] In a further experiment, HSCs-LSECs coculture system was applied to explore the possibility of inhibiting HSCs activation to prevent the loss of fenestrae and phenotype transformation of LSECs (Figure 3G). Immuno-staining of CD31 (a classic marker of capillarized LSECs) showed that HSCs pretreated with TGF-𝛽 and CS-NPs/VDG could reverse LSECs capillarization process.…”
Section: Interruption Of Hscs-lsecs Crosstalk By Cs-nps/vdg In Vitromentioning
confidence: 99%